Production of Bio-oil via Catalytic Pyrolysis of Medlar Seeds - Fatıma Topak; Mehmet Kuddusi Akalın (BioResources, 2023)
The pyrolysis of medlar seeds was performed at 350, 450, 550, and 650 °C with and without K2CO3, MgO, and expanded perlite (10 wt%). The maximum dichloromethane extract yield (6.70 wt%) was obtained at 450 °C in the pyrolysis experiments without catalyst, while the maximum bio-oil yield (50.3 wt%) was obtained at 650 °C in the presence of perlite. The dichloromethane extract and bio-oil yields decreased noticeably with the use of MgO and K2CO3. The bio-oils obtained from the non-catalytic runs mainly consisted of phenolic compounds. The use of catalysts had a noticeable effect on the composition and higher heating values of the bio-oils. The use of K2CO3 increased the relative content of 2-methoxyphenol at all tested temperatures and the relative content of 2,6-dimethoxyphenol and 2,6-dimethoxy-4-methylphenol increased with the use of expanded perlite at above 550 °C, while the use of MgO led to an increase in the relative content of 2,6-dimethoxy-4-methylphenol at above 550 °C. The bio-oil with the maximum higher heating value (30.4 MJ/kg) was obtained at 450 °C with the use of perlite. This study showed that medlar seeds are a good alternative source of waste biomass in the production of bio-oil that can be used as a biofuel.